El recurso informático el computador y su incidencia en las destrezas con criterio de desempeño de los estudiantes de la Unidad Educativa 11 de Octubre, del Cantón Urdaneta, Provincia de los Ríos - Rodríguez Macías, Jhon (2015)
The research paper, titled "The computer resource" computer "and its impact on skills judiciously performance of students in the educational unit" October 11 ", the Canton Urdaneta, Los Rios province 2015., has by the need to know the influence of the development of skills with performance criterion on learning which is justified by the need for the school to improve the learning of students, give a framework to the computer resource "computer" development the skills to performance criteria, completing the legal, conceptual and referential foundation. Its general objective is to recognize if the computer resource "computer" affects the skills to approach student performance and targets constitute detect if the computer resource "computer" affects the process of teaching and learning students The study hypothesis suggests that applying the computing resource "computer" skills to improve performance criterion of the students in the computer